Dose-response association of obesity and risk of mental health among tehranian residents: result of a cross-sectional study - Aliyu Tijani Jibril; Bahareh Jabbarzadeh Ganjeh; Amin Mirrafiei; Mahsa Firouzi; Reyhane Norouziasl; Shadi Ghaemi; Negar Bafkar; Ahmad Jayedi; Kurosh Djafarian; Sakineh Shab-Bidar (BMC, 2024)
Abstract Background Obesity and mental health issues are two of the most prevalent global public health issues for a significant portion of people. The purpose of this study was to investigate the relationship between obesity indicators and mental health in Tehran-dwelling Iranian adults. Methods We conducted a cross-sectional study on healthy Iranian adults using a convenience sampling technique. The short form of the Depression Anxiety and Stress Scale (DASS-21) was used to measure the outcome, and independent variables included body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), body adiposity index (BAI), and a body shape index (ABSI). The relationship between obesity and mental health was investigated using a multivariate logistic regression model. The non-linear dose-response relationships were evaluated using restricted cubic splines (RCS) with three knots. The Benjamini-Hochberg procedure was used to adjust for multiple testing. Results In our study of 434 participants, females made up 52% of the participants, with a mean age of 38.57 years. In all, 54.6%, 53.9%, and 56.6% were classified as having anxiety, depression, and stress respectively. Logistic regression analysis showed that the odds of mental health components including anxiety, depression, or stress was not significantly different across the tertiles of the obesity indicators. We observed a significant dose-response relationship between BAI and ABSI and the risk of anxiety (PBenjamini-Hochberg 0.028 > Pdose-response 0.023) and stress (PBenjamini-Hochberg 0.028 > Pdose-response 0.003) but not depression (PBenjamini-Hochberg 0.014 < Pdose-response 0.018). The lowest risk for anxiety was observed in people with a BAI of 28% and ABSI equal to 0.079. The risk of stress seemed to increase beyond an ABSI of 0.086. Conclusion Our findings showed no direct linear association between obesity indices and anxiety. However, a dose-response relationship was observed between BAI and ABSI and the risk of anxiety and stress, indicating the need for further investigation.